Tear film evaluation and management in soft contact lens wear: a systematic approach. (20th September 2017) - Downie, Laura E; Craig, Jennifer P
Abstract : The human tear film is a highly ordered structure consisting of a thin layer of lipid on the surface and a thicker aqueous‐mucin phase, which increases in mucin concentration toward the corneal epithelial cell layer. The health of the tear film and ocular surface influences the likelihood of being able to achieve successful contact lens wear. Contact lens discomfort and dryness are the most frequent reasons why contact lens wearers experience reduced wearing times, which can eventually lead to contact lens discontinuation. Comprehensive clinical assessment of tear film integrity and ocular surface health is therefore essential prior to commencing contact lens wear, to enable the ocular surface environment to be optimised to support lens wear. These parameters should also be evaluated over the course of contact lens wear, in order to identify any aspects requiring clinical management and ensure maintenance of optimal lens‐wearing conditions. This review summarises current knowledge relating to the effects of soft contact lens wear on the tear film and ocular surface. It also provides a systematic approach to evaluating tear film and ocular surface integrity, in order to guide the clinical management of tear film anomalies with respect to contact lens wear.